Signal mining and risk analysis of tisotumab vedotin adverse events based on the FAERS database - JuanJuan Li; Yang Zhao; Xueqin Yang; Juan Zheng; Ting Yuan; Qian Tang; Mei Guo (Scientific Reports)
Abstract Tisotumab vedotin (TV), the first antibody–drug conjugate (ADC) targeting tissue factor, was granted approval by the Food and Drug Administration (FDA) for the treatment of recurrent or metastatic cervical cancer. However, its adverse events (AE) are mainly recorded in clinical trials, lacking of real-world data. The FDA Adverse Event Reporting System database was searched retrospectively, and the TV-related AE reports from July 2021 to September 2024 were extracted. At the system organ class (SOC) level, only eye disorders (reporting odds ratio [ROR] = 11.53, proportional reporting ratio [PRR] = 9.53, information component [IC] = 3.25, and empirical bayes geometric mean [EBGM] = 9.53) and blood and lymphatic system disorders (ROR = 2.31, PRR = 2.26, IC = 1.18, and EBGM = 2.26) satisfied all four algorithms concurrently. The most common AE associated with TV is peripheral neuropathy (ROR = 23.03), while symblepharon (ROR = 1094.23) exhibited the strongest signal strength in the ROR algorithm. Notably, we identified several new signals, including cataract (ROR = 8.8) and Stevens-Johnson syndrome (ROR = 9.91). The median onset time for AEs was 21 days (interquartile range [IQR)]: 5–70 days), with the majority of AEs occurring within the first month of TV treatment. In addition to the AEs that are consistent with the instructions, we also identified some unreported signals. This discovery is expected to provide more precise guidance for the clinical application of TV.